Método do triângulo de Duval para análise dos óleos isolantes silicone e éster natural - Campos Filho, José Siqueira (2017)
This work presents a study and application of the Duval Method for alternative insulation fluids. A tool for incipient faults diagnosis is developed. The properties of silicone oil and natural ester as dielectric fluids for electric transformers are discussed. In addition, the gas-in-oil analysis is discussed. Studies found in related papers are used as database for the simulation in this work. The results are compared to the application for mineral oil analysis. The performance of the tool is tested by comparison with previously detected faults in transformers.